2022-LBA-325-ESGO Patients with newly diagnosed ovarian cancer treated with maintenance rucaparib: exploratory biomarker analysis from the phase 3 ATHENA-MONO study (GOG-3020/ENGOT-ov45; NCT03522246). (27th October 2022) - Oaknin, Ana; Kristeleit, Rebecca S; Mahdi, Haider S; Lim, Myong Cheol; de Vivo, Rocco; Salinas, Erin A; Wilson, Michelle K; Liontos, Michalis; Santin, Alessandro D; Provencher, Diane M; Demirkiran, Fuat; Willmott, Lyndsay J; et al.
Abstract : Introduction: In ATHENA-MONO, first-line (1L) maintenance treatment with rucaparib improved progression-free survival (PFS) versus placebo in patients with ovarian cancer (OC), regardless of molecular characteristics (Monk et al. J Clin Oncol. 2022). This exploratory analysis evaluated the PFS benefit of 1L maintenance rucaparib in subgroups defined by genomic biomarkers of homologous recombination deficiency, including homologous recombination repair (HRR) gene mutations, zygosity, and germline/somatic status. Methods: Patients with high-grade OC who underwent cytoreductive surgery and completed 1L platinum-doublet chemotherapy with a partial or complete response were randomised 4:1 to oral rucaparib 600 mg BID or placebo. Mutations in BRCA1, BRCA2, and 28 other genes in the HRR pathway (Coleman et al. Lancet . 2018), and zygosity status, were identified via next-generation sequencing of tumor tissues (Foundation Medicine). BRCA germline/somatic status were determined by germline sequencing (Ambry Genetics). The primary endpoint was investigator-assessed PFS per RECIST. Results: Deleterious mutations in BRCA1 and BRCA2 were detected in 13.9% (75/538) and 7.4% (40/538) of patients, respectively. PFS was longer with rucaparib compared with placebo in both BRCA1 (HR=0.39; 95% CI=0.14–1.08) and BRCA2 (HR=0.46; 95% CI=0.13–1.69) subgroups. Rucaparib PFS benefit was observed regardless of BRCA mutation type: short variants (frameshift, nonsense, splice site, missense) or large structural events (homozygous deletions, large rearrangements). BRCA mutations were further classified by germline (12.6%; 68/538), somatic (6.1%; 33/538), or unknown (2.6%; 14/538). PFS was longer with rucaparib compared with placebo in germline (HR=0.33; 95% CI=0.10–1.12) and somatic (HR=0.65; 95% CI=0.18–2.39) BRCA subgroups. Deleterious mutations in non-BRCA HRR genes were detected in 11.2% (60/538) of patients, with a PFS benefit of rucaparib versus placebo (HR=0.59; 95% CI=0.24–1.43). Conclusions: Exploratory biomarker analyses confirmed benefit with 1L maintenance rucaparib in patients with advanced OC harbouring different types of deleterious mutations in BRCA and non-BRCA HRR genes.